Effect of Different Polishing Systems on the Surface Roughness and Gloss of Novel Nanohybrid Resin Composites - Soliman, Hanan A. N.; Elkholany, Naglaa Rizk; Hamama, Hamdi H.; EL-Sharkawy, Fatma M.; Mahmoud, Salah H.; Comisi, John C. (European Journal of Dentistry, 2020)
Objectives To evaluate the surface roughness and gloss of three nanohybrid resin composites after polishing with three different polishing systems.Materials and Methods A total number of 112 disc specimens (10 × 3 mm) were prepared from nanohybrid—Empress Direct (ID), Grandio (GR), Filtek Z350 (Z350) and a microhybrid resin composite restorative materials—Filtek Z250 (Z250). Following 24-hour storage in 37°C distilled water, each composite group (n = 28) was assigned into four groups (n = 7) according to finishing/polishing (F/P) system: Mylar strip, Optrapol, Politip, and Sof-Lex (SL). The surface roughness (Ra, mm) was measured by a novel three-dimensional method using an image analysis software attached to an environmental scanning electron microscope. A glossometer was used to measure the surface gloss.Results Statistical analysis used was ANOVA test. Two-way Anova test revealed that the “type of composite” and “F/P techniques” had a significant effect on both surface roughness and gloss of the tested resin composite materials (p < 0.05). Tukey’s post hoc test showed that ID, GR, and Z350 revealed lower surface roughness and higher surface gloss than Z250 within the same polishing system (p < 0.05). Sof-Lex polishing discs produced the lowest surface roughness and highest surface gloss values compared with Optrapol and Politip (p < 0.05).Conclusion The tested F/P systems provided comparable surface roughness and gloss for nanohybrid composites. The Sof-Lex system provided the best surface roughness and gloss for nanohybrid composites.
Keywords: microhybrid; nanohybrid; roughness; gloss; polish; resin composite restorative material